Pengaruh Model Pembelajaran Learning Cycle 7E terhadap Keterampilan Berpikir Kritis Peserta Didik di SMPN 1 Kampar Kiri Tengah - Cahyani Elvira; Rian Vebrianto (Journal of Instructional Development Research, 2021)
This study aims to determine whether there is an effect of the implementationf the 7E learning model on critical thinking skills of students. The form of this research is Quasi experiment with Nonequivalent Control Group Design, which is a form of research that uses one experimental class and one control class to determine the difference between two variables. The population in this study were all class VII with the sample selection was purposive sample. The sample in this study consisted of 2 groups, namely class VII C as the experimental class which received the 7E Learning Model strategy treatment (32 students) and class VII B (30 students) applied conventional learning. The data was collected by means of a pretest and posttest essay test, and the data obtained were analyzed using independent sample t-test. The results of the final data processing obtained Sig. (2-tailed) of 0.000 less than 0.05, it can be concluded that Ha is accepted and Ho is rejected. The conclusion from the results of this data processing is there is an effect of the application of the 7E learning model on students' critical thinking skills. Based on the results of this study, there are several implications for analysis of critical thinking skills of students. First, students are expected to be able to respond to the importance of these skills to be mastered as a foundation for facing challenges in the 21st century, this can be done by continuing to hone skills by training themselves to be active through learning in the classroom like being involved in questioning, analyzing and conclusions and believe what is done in the presence of a sound foundation of knowledge. Then the implications for the special education institution of SMPN 1 Kampar Kiri Tengah, can be an input for schools to continue to improve the quality of learning after seeing a picture of students' critical thinking skills.